Thermal and electrical analysis of SiGe thermoelectric unicouple filled with thermal insulation materials. (April 2018) - Li, Jing; Xiang, Qingpei; Ze, Rende; Ma, Mingyang; Wang, Shumiao; Xie, Qilin; Xiang, Yongchun
Highlights: Crucial design parameters were evaluated for their impact on the SiGe thermoelectric unicouple performance. Thermal insulation filler is beneficial to avoid radiation heat loss and maintains conversion efficiency at ∼7%. A thermoelectric generator consisted with SiGe unicouples and cooling fins is optimized. Abstract: Thermoelectric performance of SiGe unicouple filled with four kinds of thermal insulation materials is simulated using finite element method. Crucial design parameters including thermoelectric leg length L, space ti, hot side temperature Th within 1073–1223 K and cold side temperature Tc within 573–773 K were evaluated for their impact on the unicouple performance. Unicouple models consisted of SiGe served in RTG on board Cassini spacecraft (Cassini SiGe) and home-made ball milled SiGe (BM SiGe) are analyzed, respectively. It is found that the power output per unit area PA, heat absorption per unit area QhA and heat released per unit area QcA are inversely proportional to leg length and space area between legs. The conversion efficiency η of SiGe thermoelectric legs is ∼7.5% at Th = 1223 K (1173 K) and Tc = 573 K. η of unicouple will decrease to below 1% if there is no fillers in the space between legs. For unicouple filled with thermal insulation materials, radiation heat is shielded, and heat flow from filler will lead to a η decrease of 0.07–0.5%, where ηunicouple of 7.09% and 6.89% can be obtained, respectively. A model calculating system mass and power density for thermoelectric generator is built, and is used to optimize the system.